MINING INDUSTRY OF UKRAINE: CURRENT STATE AND DEVELOPMENT PROSPECTS - VLASENKO, Ivan; HALACHENKO, Oleksandr; BONDAR, Tetyana; GLINSKA, Ruslana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
An important part of Ukraine’s economy is the mining industry, which occupies leading positions both in the structure of gross domestic product (GDP) and in the structure of exports. The war significantly affected the mining industry of Ukraine. Many businesses have shut down due to security risks, infrastructure destruction and loss of workers. The article examines the share of the mining industry and the development of quarries in the GDP of Ukraine. In modern conditions, the Ukrainian mining industry acquires new importance not only in terms of the strategic development of the state’s economy, but also in terms of its defense capability and prospects for post-war reconstruction. The analysis of the direct contribution of the mining industry to the GDP of Ukraine was carried out; export value of mining industry products; the total volume of payments of extractive industries to the state; the volume of capital investments in all mining industries. The balance reserves and the total volume of extraction in 2021 of the main minerals of Ukraine were considered. For many years, Ukraine, having its own reserves, imported critical for industry (including defense) rare earth metals, mineral raw materials, etc. The prospects for the use of Ukrainian mineral deposits are analyzed. The strategic goal of the mining industry today is to establish domestic production of metal products from titanium (rolled, assembly, etc.), capable of creating greater added value compared to the production of pigments based on titanium dioxide. Ukraine is one of the five leading countries in the world in terms of explored graphite reserves and is one of its largest exporters. For the needs of recovery, it is important to increase the production of construction products using significant internal reserves of quartz sand (for the production of sheet glass), building stone, and refractory clay. Prospects for lithium mining and processing in Ukraine are determined by the constant growth of demand for it, in particular from the EU. The main problems of mining and processing enterprises that arose in connection with the full-scale invasion of the Russian Federation are highlighted. It is shown that a significant share of the added value of export of products from Ukraine is created in the mining and processing industry sector, which strengthens the economic and military position of Ukraine. The priorities of Ukraine should be the involvement of European technologies of intellectual mining, processing, creation of production chains within the country, search and development of joint projects with the EU regarding the production of critical products. Today, mining and processing enterprises face such problems as: the destruction of production lines due to military strikes, the outflow of labor due to forced emigration and mobilization, the interruption of logistics chains of purchases and sales, as well as insufficient production equipment to restore damaged equipment. In addition, the presence of high military risks prevents the normal course of foreign economic activity, which deepens the crisis phenomena in the sector. Mining and processing industries of ukraine at the current stage are strategic industries, taking into account the specific needs of the war economy and post-war reconstruction. These industries have a large-scale positive impact on the development of other sectors of the economy, have a high potential for growth in the ukrainian economy, contribute to the development of technologies, the reduction of social tensions and the level of unemployment in the conditions of war and during post-war reconstruction.